E-Commerce Logistics Intelligent Warehousing System Solution Based on Multimedia Technology - Huajin Liu; Zhenlong Hu; Jianhua Hu (Journal of Electrical and Computer Engineering)
In recent years, with the integration and development of the internet and various industries, the social economy has begun to develop toward diversification. The rise of e-commerce logistics has driven the transformation and upgrading of the manufacturing industry and injected new vitality into e-commerce. It also promotes the new development of cargo warehousing as one of the important components. Traditional warehousing began to gradually develop toward intelligent informatization, relying on emerging science and technology. Smart warehousing also brings valuable development opportunities and challenges to the manufacturing industry. On the basis of the existing achievements, this paper proposes a solution of an intelligent warehousing system for e-commerce logistics based on multimedia technology. It, firstly, introduces the structure of the intelligent warehousing system in detail, and then, it analyzes the requirements for the functions of the intelligent warehousing system based on multimedia technology. It includes user management, receiving business, storage business, tally business, and outbound business. In the end, the intelligent warehousing system based on multimedia technology and the traditional intelligent warehousing system are compared and tested for system function and experience. The test results show that the work efficiency of the intelligent warehousing system based on multimedia technology is significantly higher than that of the traditional intelligent warehousing system. In terms of user experience, the performance of the intelligent warehousing system based on multimedia technology has reached 8 points and above. It proves its usefulness and effectiveness.